CdTe based nanocomposite materials for biological imaging - Byrne, Stephen J. (Trinity College (Dublin, Ireland). School of Chemistry, 2008)
The main goal of this research is to develop new CdTe QD based nanomaterials and demonstrate their potential for biological applications, in particular their use as fluorescent bioimaging tools. This work involves the synthesis and characterisation of CdTe QDs using various thiol capping agents, modification of QDs to improve their luminescence efficiencies, stability and biocompatibility, conjugation of QDs to drug molecules and investigations into their photophysical behaviour, distribution and toxicity in live cells.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin